2008
DOI: 10.1248/bpb.31.51
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Saururus chinensis (LOUR.) BAILL on the Development of Atopic Dermatitis-Like Skin Lesions in NC/Nga Mice

Abstract: The present study was performed to examine whether the leaves of Saururus chinensis (LOUR. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…10) Studies have shown that S. chinensis has various activities, including anti-inflammatory, anti-oxidant, 11,12) antiangiogenic, 13) anti-asthmatic, 14) and anti-hypertensive 15) activities, as well as therapeutic activity against atopic dermatitis. 16) Among the bioactive compounds isolated from S. chinensis, manassantin A is a major phytochemical composition that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACA T) inhibitory activities. 17) Multiple reports have also described manassantin A as having various beneficial effects, including the abilities to reduce hyperpigmentation disorders, prevent atherosclerosis, and lower cholesterol.…”
mentioning
confidence: 99%
“…10) Studies have shown that S. chinensis has various activities, including anti-inflammatory, anti-oxidant, 11,12) antiangiogenic, 13) anti-asthmatic, 14) and anti-hypertensive 15) activities, as well as therapeutic activity against atopic dermatitis. 16) Among the bioactive compounds isolated from S. chinensis, manassantin A is a major phytochemical composition that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACA T) inhibitory activities. 17) Multiple reports have also described manassantin A as having various beneficial effects, including the abilities to reduce hyperpigmentation disorders, prevent atherosclerosis, and lower cholesterol.…”
mentioning
confidence: 99%
“…baill (SC), viscum album L. (VA), and houttuynia cordat are main active compounds in TMC. SC is the herb that used for treating various skin diseases including atopic dermatitis (Choi et al, 2008) and it has been reported that SC could possesses a number of biological effects, such as anti-allergic and antiinflammatory (Scalbert et al, 2000;Parr et al, 2000). VA has been reputed against hypertension, arthritis, and immune system stimulation (Orhan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Saururus is a perennial herbaceous plant used in Korean folk medicine for the treatment of various conditions such as edema, jaundice, gonorrhea and used has been employed as an antipyretic, diuretic, and anti-inflammatory agent (Choi et al, 2008). It has been shown to have anti-oxidant activity (Y. S. Lee et al, 2004) and has been used in the management of various skin diseases including AD in Eastern countries.…”
Section: Saururus Chinensis Baillmentioning
confidence: 99%